Seasonal prey taxa and size selection and drivers of age-0 walleye ontogenetic diet shifts - Casey W. Schoenebeck; Keith D. Koupal; Brian C. Peterson; Chris S. Uphoff; Zach Woiak; Brett T. Miller; Melissa R. Wuellner; Joshua W. Kreitman (Journal of Freshwater Ecology)
Prey abundance and size vary seasonally, creating a dynamic connection between predator and prey. The natural complexity related to consuming multiple prey types as fish undergo ontogenetic diet shifts combined with the frequent sampling and substantial laboratory time investment required to investigate seasonal predator-prey dynamics limits understanding of seasonal prey availability and age-0 prey taxa and size selection. Our study used frequent prey sampling spanning a four-year period to understand which prey taxa and sizes are seasonally available to age-0 walleye Sander vitreus, which were sampled from May to November across all four years of this study to document food habits and prey sizes. Consumed prey were then compared to available prey within the reservoir to evaluate prey taxa and size selection. Age-0 walleye seasonal food habits were consistently simplistic as age-0 walleye in this study largely consumed a single zooplankton taxa (calanoida) and then shifted directly to piscivory where they again focused consumption on a single taxa, and age group (age-0 gizzard shad Dorosoma cepedianum) while passing over available benthic macroinvertebrates. The ontogenetic shift to larval gizzard shad coincided with peak larval shad availability. Interestingly, age-0 walleye were size selective for both prey types, selecting the largest calanoida available when zooplanktivorous but consuming some of the smallest age-0 gizzard shad despite increasing gape size that would have allowed for consumption of larger shad.